The quest for regional accreditation of art and design education in the Arab Countries - Sanaa Ashour; Ahmed Said Ghonim (Cogent Arts & Humanities, 2017)
In recent years, international accreditation has become an important part of quality management in higher education. However, given risks including increasing bureaucratisation, outdated systems and high costs, international accreditation remains problematic in the developing countries that might have relatively underdeveloped higher education systems and less integrated into the world system than developed countries. Focusing on the Arab countries, this paper assesses whether specialised programme-level accreditation of Art and Design programmes by international bodies such as the National Association of Schools of Art and Design (NASAD) or the Council for Interior Design Accreditation (CIDA) or building a consortium similar to the Association of Independent Colleges of Art and Design (AICAD), enhances the quality of practical studio-based classes in such programmes in Egypt and the United Arab Emirates (UAE) as case studies. Given the importance of Art and Design for economic development, our investigations conclude that there is a need for a regional accrediting body adapting international standards, while accommodating Middle East distinct cultural aspect to regulate, and enhance quality of Art and Design Education in the Middle East.